A realidade virtual no desenvolvimento das capacidades de falar em público: uma perspetiva na área da formação - Vasconcelos, Daniela Filipa Almeida Baptista Borges (2022)
Introduction: Although it causes fear, insecurity, and stress, public speaking strengthens the per-sonal field and, above all, the professional field. In view of this, public speaking courses received a large response because they provide strategies and tools that together improve oral skills. Howev-er, there is a tendency towards virtual reality (VR), whose devices promptly reduce nervousness and anxiety. Objectives: The dissertation focused on the elaboration of training programs that, accompanied by virtual reality, would develop the public speaking ability. In parallel, it was intended to have a peda-gogical view at the usefulness of VR in the improvement of communicative skills. Methods: Initially, scoping reviews were carried out, which simultaneously explored the character-istics and impacts of training on public speaking practices. The first focused on the observation of usual courses and, in turn, the second focused on courses with virtual reality. Furthermore, an ex-ploratory investigation proved itself advantageous for the analysis of software in the area. Results/Conclusions: The scoping reviews attested to the importance of training programs in im-proving oratory, however, the use of virtual reality in education and training reflects a new proce-dure, needing investigation. Regarding the exploratory research, nine applications were found that, in general, facilitate the progress of users.